2012
DOI: 10.1111/ger.12036
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of moment structures for assessing relationships among perceived chewing ability, dentition status, muscle strength, and balance in community‐dwelling older adults

Abstract: The findings observed in this study present a possible importance of dental status and perceived chewing ability for the onset of disability by influencing physical performance in community-dwelling older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…Several studies have reported on the relationship between chewing ability and grip strength/physical performance, and on the relationship between tongue muscle thickness and sarcopenia, but there have been no reports addressing the possible relationship between chewing ability and sarcopenia.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported on the relationship between chewing ability and grip strength/physical performance, and on the relationship between tongue muscle thickness and sarcopenia, but there have been no reports addressing the possible relationship between chewing ability and sarcopenia.…”
Section: Introductionmentioning
confidence: 99%
“…Another recent study reported a relationship between certification of long-term care insurance and self-rated chewing ability. The result of the Kaplan–Meier analysis for individuals aged 65 to 79 years clearly demonstrated that the proportion of individuals not certified for long-term care insurance significantly declines in those with self-rated fair or poor masticatory ability compared with those having good mastication (Moriya, Notani, Murata, Inoue, & Miura, 2014). A Cox proportional hazard analysis also shows that the certification for long-term care insurance was 1.87-fold (CI = [1.07, 3.27]) higher in the individuals with fair or poor masticatory ability in comparison with those with adequate ability (Moriya et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The result of the Kaplan–Meier analysis for individuals aged 65 to 79 years clearly demonstrated that the proportion of individuals not certified for long-term care insurance significantly declines in those with self-rated fair or poor masticatory ability compared with those having good mastication (Moriya, Notani, Murata, Inoue, & Miura, 2014). A Cox proportional hazard analysis also shows that the certification for long-term care insurance was 1.87-fold (CI = [1.07, 3.27]) higher in the individuals with fair or poor masticatory ability in comparison with those with adequate ability (Moriya et al, 2014). A 6-year follow-up study on rural community–dwelling older adults in Japan by Shinkai et al (2003) demonstrated that depression of basic activity of daily living (ADL) and iADL were 1.88-fold (CI = [1.26, 2.82]) and 2.22-fold (CI = [1.50, 3.27]), respectively, higher in individuals with poor chewing ability in comparison with those with better ability.…”
Section: Discussionmentioning
confidence: 99%
“…Takata et al identified a relationship between postural balance and masticatory ability by evaluating by the number of chewable foods; their study suggested that higher masticatory ability is associated with better posture. Additionally, Moriya et al found a positive correlation between self‐assessed masticatory ability and postural balance; relationships have also been reported between postural balance and various factors: perceived chewing ability, dentition status and muscle strength …”
Section: Introductionmentioning
confidence: 96%
“…To more objectively evaluate dynamic chewing behaviour, this study used the mixing ability index (MAI) to quantitatively measure masticatory function. Additionally, postural balance has largely been assessed using static methods; for example, prior studies have measured the duration for which participants can maintain balance while standing on one leg . However, postural balance can be assessed using static and/or dynamic methods.…”
Section: Introductionmentioning
confidence: 99%